OBSERVATIONS ON SOME PHYSICO-CHEMICAL FEATURES OF THE CHILKA LAKE - Banerjee, A C; Choudhury, N C Roy (Indian Journal of Fisheries, 2011)
A STUDY of certain physico-chemical features of Chilka Lake was commencedby the Chilka Investigation Unit in April, 1957, with a view to understandthe pattern of iish migration into and their movements within the lake;their concentration in different sections of the lake and to correlate, if possible,the fluctuations in the abundance of the different commercial specieswith the physico-chemical characters of the environment. The presentpaper delineates the observations made in this regard during the periodApril, 1957 to March, 1961.